Prescribers’ Compliance to Human Serum Albumin Usage Criteria and Its Implication on Cost Saving - Sukkha S. (2023)
Human serum albumin (HSA) is a commonly used product with high impact on healthcare expenditure. Little is known regarding the appropriateness of HSA use in healthcare system. This study aimed to assess prescriber’s compliance to the approved HSA criteria. Potential cost saving was also estimated. A cross-sectional study was performed in a tertiary care, university hospital in Bangkok in 2019. Prescriptions for HSA for all adult patients along with corresponding medical records were reviewed and assessed against the approved HSA criteria. Deviation from the criteria was used to estimate the potential cost saving. A total of 688 prescriptions were reviewed, 200 prescriptions met the inclusion criteria and were included in the analysis. Among six indications in the approved criteria for HSA, the rates of criteria compliance ranged from 48 to 90%. Hypoalbuminemia was found to be the main reason for inappropriate use. The estimated cost saving from inappropriate HSA use was €3,543 (€59 per prescription). Significant deviation from the approved criteria of HSA use was seen in a Thai hospital and significant cost saving can be made by increasing the compliance to the criteria. A practice improvement initiative to promote rational use of HSA is warranted.